KSP siRNA/paclitaxel-loaded PEGylated cationic liposomes for overcoming resistance to KSP inhibitors - 이진주; Ahn Hyung Jun (대한화학회, 2020)
Despite the promising anticancer effects of kinesin spindle protein (KSP) inhibition, functional plasticity of kinesins induced resistance against KSP inhibitors in a variety of cancers, leading to clinical failure. Additionally, paclitaxel is a widely used anticancer agent, but drug resistance has limited its use in the recurrent cancers. To overcome resistance against KSP inhibitors, we paired KSP inhibition with microtubule stabilization using KSP siRNA and paclitaxel. To enable temporal co-localization of both drugs in tumor cells in vivo, we exploited PEGylated cationic liposomes carrying both simultaneously. Drug synergism study shows that resistance against KSP inhibition can be suppressed by the action of microtubule-stabilizing paclitaxel, because microtubule stabilization prevents a different kinesin Kif15 from replacing all essential functions of KSP when KSP is inhibited. Our combination therapy showed more effective antiproliferative activity in vitro and in vivo than either paclitaxel or KSP siRNA alone. Ultimately, we could observe significantly improved therapeutic effects in the drug-resistant in vivo models, including cell line and patient-derived xenografts. Taken together, our combination therapy provides a potential anticancer strategy to overcome resistance against KSP inhibitors. Particularly, this strategy also provides an efficient approach to improve the therapeutic effects of paclitaxel in the drug-resistant cancers.
Keywords: liposome; drug-resistance; combination therapy; KSP siRNA; paclitaxel